Tindak Pidana Fidusia Dan Penegakan Hukumnya di Kota Gorontalo - Dwi Intan Lestari Ahmad; Lisnawaty W Badu; Julisa Aprilia Kaluku (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research discusses the effectiveness of law enforcement against fiduciary crimes in Gorontalo City and the factors that influence its enforcement. The method used in this research is empirical, using field data and facts, and analyzed descriptively qualitatively. Based on the research results, law enforcement against fiduciary crimes in the city of Gorontalo has not been effective, this is due to a trend of increasing and increasing cases from year to year (from 2022 to 2023). Based on the existing case data regarding fiduciary crimes from year to year, where in 2020 there were 17 cases and in 2021 there were 45 cases, it can be said that this has increased by almost 300% (percent). Meanwhile in 2022 there will be a decrease from 45 cases to 30 cases. This means that it only experienced a decrease of around 35% (percent) compared to the previous large increase. However, this number then increased again to 54 cases in 2023 (until August), so that the upward trend this year is around 95% (percent). Based on this, law enforcement against this criminal act has not been effective because it has not completely decreased every year but instead there has been a significant increase. Factors that influence law enforcement for fiduciary crimes at the Gorontalo City Police Department are the identity of the perpetrator being unclear and running away, collateral objects that are difficult to trace, as well as inadequate human resources and infrastructure.